The divine female and the mystique of the moon: three-phases gender-theory in theosophical kabbalah - Idel, Mosheh (Archaeus, 2016)
The present study describes the emergence of a Kabbalistic theory of gender, as a development from the Rabbinic ritual of blessing the moon, that is based on a myth that describes the diminution of the moon. In the pre-Kabbalistic text and in the Kabbalistic ones, it is possible to discern three different phases in the cycle of the moon and the divine Female hypostasis: the equality of the Male and Female, and Sun and Moon, the decrease of the Female/moon and finally the renewal or the restoration of Her status. These three phases should be understood as part of one unit, and are presented as a model for understanding the status of the Female in the Kabbalistic school of Nahmanides and in his many followers, who influenced a series of later Kabbalists.